Numerical investigation on the salient features of flow over standard notchback configurations using scale resolving simulations. (15th October 2020) - Chode, K.K.; Viswanathan, H.; Chow, K.
Highlights: SBES and SDES models agree reasonably well with experimental data for SAE T20 and SAE T40. SBES appears to resolve the flow structures marginally better than SDES. The transition from RANS to LES in SBES was found to be rapid and definitive in SSL. Flow features change significantly with a change in backlight angle. For SAE T30, the agreement between the model and experiment is less promising. Abstract: We present a detailed numerical investigation on the salient features of flow over an SAE reference body with several backlight angles representing a standard notchback geometry using Scale Resolving Simulations (SRS) such as the SBES and the SDES. A grid evaluation study is performed for the SAE Notchback geometry with 20° backlight angle with a Reynolds number ( Re ) of 6.57 × 10 5 based on the height of the body. Various aerodynamic parameters and flow structures are compared against the previously published experimental results to evaluate the performance of the numerical predictions and against the unsteady k – ω SST model. Both SBES and SDES models agree well with the previously published wind tunnel results, exhibit a well-preserved modelled RANS layer, and numerically show minor differences between them. However, the transition from RANS to LES in the separated shear layer (SSL) appears to be marginally robust with SBES. Our numerical results demonstrate that with an increase in the backlight angle, the strength of trailing vortex tends to reduce on one side compensated by an increase on the other side of the model. As a consequence, the SSL shows a non-symmetrical flow feature behind the vehicle for the backlight angles of 30° and 40° as detailed in the experimental result and suitably predicted by the numerical results. We highlight that within the scope of this study, both the SRS models have shown to be accurate and reliable in predicting the aerodynamic force coefficients and flow features observed in experiments.